Intermittent Propagation of Upward Positive Leader Connecting a Downward Negative Leader in a Negative Cloud‐to‐Ground Lightning. Issue 24 (21st December 2019) - Srivastava, Abhay; Jiang, Rubin; Yuan, Shanfeng; Qie, Xiushu; Wang, Dongfang; Zhang, Hongbo; Sun, Zhuling; Liu, Minyuan
Abstract: Both upward positive connecting leader (UPL) and downward negative leader (DNL) involved in a lightning striking the 325‐m meteorology tower were captured by using a high‐speed video camera with 2.7‐μs temporal resolution and 1‐m spacial resolution, in association with electromagnetic field measurements. The UPL initiated around 1.6 ms prior to the attachment when the DNL was outside the field of view of the camera, and 38 hop forwards with backward re‐illumination through the UPL channel were identified. As the stepped DNL approached, 34 space stems were observed in front of the leader tip during 0.62‐ms period prior to the attachment, while, based on the present observation system, no visible space stem was found throughout the intermittent UPL propagation. The 2‐D propagation speed of the UPL and DNL was 1.16 × 10 5 and 3.6 × 10 5 m/s, within channel extensions of 100 and 95 m, respectively. For the UPL, the inter‐step interval was longer in its initial development while the step length was similar throughout the propagation. Several steps of DNL could be identified within an inter‐step of UPL, and vice versa. The different intermittent behaviors of negative and positive leaders with temporal‐inconsistent steps suggest that their stepping was independent from each other. When the DNL was very close to the UPL, the DNL can induce and support the UPL development by enhancing the overall electric field. However, it seems that the generation of space stems and their bridging to the DNL, as involved in the DNL stepping, might not the direct cause of the UPL intermittence. Key Points: Simultaneously, captured downward negative and upward connecting positive leader exhibited different intermittent propagating features Thirty‐eight hop forwards and re‐illumination in positive leader growth were identified with images in 2.7‐μs temporal and 1‐m spatial resolution Positive leader intermittence was not temporally consistent with negative leader stepping of which space stems bridged to the channel